2000
DOI: 10.1002/1096-9861(20001218)428:3<558::aid-cne11>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Vagal afferent innervation of smooth muscle in the stomach and duodenum of the mouse: Morphology and topography

Abstract: Intraganglionic laminar endings (IGLEs) and intramuscular arrays (IMAs), the two putative mechanoreceptors that the vagus nerve supplies to the gastrointestinal smooth muscle, have been characterized almost exclusively in the rat. To provide normative inventories of these afferents for the mouse, the authors examined the endings in the stomach and small intestine of three strains used as backgrounds for gene manipulations (i.e., C57, 129/SvJ, and WBB6). Animals received nodose ganglion injections of wheat germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
163
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(189 citation statements)
references
References 24 publications
(31 reference statements)
21
163
1
1
Order By: Relevance
“…However, inhibitory vagal fibers also innervate the stomach such that a decrease in vagal inhibitory activity could be responsible as well. Interestingly, the communication between the vagus and ICC is bidirectional in that the vagal afferent fibers have synapse-like contact with ICC [20,21]. Our observation that the meal induced an increase in heart rate, consistent with findings in another recent study [22], could also the result of a meal-induced increase in sympathetic activity.…”
Section: Discussionsupporting
confidence: 80%
“…However, inhibitory vagal fibers also innervate the stomach such that a decrease in vagal inhibitory activity could be responsible as well. Interestingly, the communication between the vagus and ICC is bidirectional in that the vagal afferent fibers have synapse-like contact with ICC [20,21]. Our observation that the meal induced an increase in heart rate, consistent with findings in another recent study [22], could also the result of a meal-induced increase in sympathetic activity.…”
Section: Discussionsupporting
confidence: 80%
“…IGLEs are found in the oesophagus, stomach, small intestine and in reduced numbers in the upper colon. 28,29 Each axon gives rise to several IGLEs within a small area 24,25 but might also innervate widely separated areas. 30,31 IGLEs have been suggested to detect shear forces between orthogonally arranged (longitudinal and circular) muscle bundles coupled to either face of the ganglion.…”
Section: Vagal Intraganglionic Laminar Mechanoreceptorsmentioning
confidence: 99%
“…Intramuscular arrays (IMA) enter circular or longitudinal muscle layers, run parallel to respective muscle fibers, and bifurcate to create an array of parallel terminal elements in stomach and sphincters (28). In the stomach, these terminal elements consist of interconnected parallel axonal telodendria that are arrayed in close proximity to one another and that form appositions with interstitial cells of Cajal (ICC) (20). Recent ultrastructural studies have identified synapse-like connections between IMA nerve varicosities and intramuscular ICC (ICC-IM) (29).…”
mentioning
confidence: 97%